PELATIHAN WIRAUSAHA BUDIDAYA RUMPUT LAUT EUCHEUMA COTTONII DI DESA KOLORAY KECAMATAN MOROTAI SELATAN - Sukarmin Idrus; Hartati Kapita; M Reza Kusman; Fitro Darwis; Miswar Papuangan; Titien Sofiati; Maujud Popa (Jurnal Abdi Insani, 2023)
Morotai Island is a seaweed cultivation development area. However, currently there are obstacles faced by cultivators, namely ice-ice disease and yield management. Efforts to optimally manage and utilize the potential for seaweed cultivation on small islands can be carried out through fostering small, medium and micro enterprises (MSMEs). The purpose of this service is to provide assistance in the process of cultivating good seaweed, while the benefits derived from this service are expected to produce sustainable seeds and create jobs for coastal communities. The implementation of this service was carried out in Koloray Village, South Morotai District, Morotai Island Regency, North Maluku. The subject of this activity is the Koloray Village Seaweed Farmer Group. The process of implementing this service includes: mapping the potential for cultivation land, mapping aspects of community human resources, program socialization, and institutional strengthening training in implementing seaweed cultivation. The results of this activity were mapping the location of seaweed cultivation so that locations that had previously been planted were obtained, taking into account accessibility, the area of the planting area and protection from waves, in addition to observing the quality of the waters including parameters of temperature, salinity, pH, brightness, depth and bottom of the waters. considered suitable according to good qualifications. For sustainability and success in business, institutional strengthening is also carried out in running a business as well as monitoring and evaluation. With this activity, the community, especially the cultivator group, have been able to determine the location selection, the selection of the cultivation method and the ability to overcome the main problems of seaweed cultivation, in this case the parrotfish, by changing the method from basic stakes to the floating net raft method.